2003
DOI: 10.1261/rna.2145103
|View full text |Cite
|
Sign up to set email alerts
|

3′-processing of yeast tRNATrp precedes 5′-processing

Abstract: Previous analyses of eukaryotic pre-tRNAs processing have reported that 5-cleavage by RNase P precedes 3-maturation. Here we report that in contrast to all other yeast tRNAs analyzed to date, tRNA Trp undergoes 3-maturation prior to 5-cleavage. Despite its unusual processing pathway, pre-tRNA Trp resembles other pre-tRNAs, showing dependence on the essential Lsm proteins for normal processing and efficient association with the yeast La homolog, Lhp1p. tRNA Trp is also unusual in not requiring Lhp1p for 3 proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 46 publications
1
35
0
Order By: Relevance
“…In contrast, in cells lacking Rrp6 and, more visibly, Trz1 and both Rrp6 and Rex2, the increased level of some 5 ′ /3 ′ -ptRNAs, symptomatic of the defect in 5 ′ -end processing, was also detected. Although inhibition of 3 ′ cleavage when RNase P processing is reduced has been observed repeatedly (Lee et al 1991;Lygerou et al 1994;Kufel and Tollervey 2003), the reverse has not been reported. Moreover, tRNase Z has been shown to efficiently cleave only 5 ′ -processed pre-tRNAs, and human tRNase Z activity in vitro is inhibited by the presence of longer 5 ′ extensions (Kunzmann et al 1998;Nashimoto et al 1999;Schierling et al 2002;Dubrovsky et al 2004).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In contrast, in cells lacking Rrp6 and, more visibly, Trz1 and both Rrp6 and Rex2, the increased level of some 5 ′ /3 ′ -ptRNAs, symptomatic of the defect in 5 ′ -end processing, was also detected. Although inhibition of 3 ′ cleavage when RNase P processing is reduced has been observed repeatedly (Lee et al 1991;Lygerou et al 1994;Kufel and Tollervey 2003), the reverse has not been reported. Moreover, tRNase Z has been shown to efficiently cleave only 5 ′ -processed pre-tRNAs, and human tRNase Z activity in vitro is inhibited by the presence of longer 5 ′ extensions (Kunzmann et al 1998;Nashimoto et al 1999;Schierling et al 2002;Dubrovsky et al 2004).…”
Section: Discussionmentioning
confidence: 96%
“…This has been demonstrated, for example, in S. cerevisiae, where mutations in RNase P block maturation of both 5 ′ and 3 ′ ends (Lee et al 1991;O'Connor and Peebles 1991;Furter et al 1992;Lygerou et al 1994). Nevertheless, several exceptions to this order of processing have been reported, including some tRNAs in mouse and wheat germ extracts (Rooney and Harding 1986;Arends and Schön 1997), and in vivo processing of yeast tRNA Trp (Kufel and Tollervey 2003). tRNA splicing and end processing are not strictly ordered, but in yeast wild-type cells, the rate of splicing is slower, and the presence 3 of the 5 ′ leader has been reported to slow down intron removal; therefore, mainly unspliced and end-processed intermediates are detected (O'Connor and Peebles 1991; Kufel and Tollervey 2003;Hiley et al 2005).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Saturation of RNase P RNA Is Not a Reason for Pre-tRNA Accumulation in the Absence of Maf1-First, we explored the possibility that accumulation of untrimmed initial transcripts in maf1⌬ cells is due to saturation of RNase P, which removes the 5Ј leader preceding removal of the 3Ј trailer (40). RPR1, the gene encoding the RNA subunit of RNase P, is transcribed by Pol III (41).…”
Section: Accumulation Of Pre-trna Is Correlated With Loss Of Nuclearmentioning
confidence: 99%
“…In eukaryotes, tRNAs are transcribed in the nucleus as primary transcripts that undergo extensive processing, chemical modification, and subcellular trafficking to produce the mature tRNAs that function in cytoplasmic translation. In the yeast Saccharomyces cerevisiae, tRNA transcription in the nucleolus (1), with one exception (2), is followed by removal of the 5′ leader sequence by RNase P (3). The 3′ trailer is subsequently removed endonucleolytically, presumably by tRNase Z (4-6), and/or exonucleolytically by Rex1 (7,8).…”
mentioning
confidence: 99%